Cretaceous metamorphism, magmatism and shearing in the Waipuna Valley, directly south of the Reefton Goldfield - Ritchie, T.; Scott, J.; Muhling, J.; Kennedy, Allen (Taylor and Francis Asia Pacific, 2015)
Rocks in the Waipuna Valley in Westland show that the area immediately south of the Reefton Goldfield has been dramatically affected by Cretaceous tectonism. The main lithology in the Waipuna Valley is metasedimentary Greenland Group that is here subdivided into four types (I, II, III and IV). Type I contains abundant detrital grains with a weak Palaeozoic greenschist facies overprint and is compositionally indistinguishable from unmineralised Greenland Group within the goldfield. Type II contains detrital grains, but also a weak amphibolite facies foliation or, where proximal to granitoid intrusions, a hornfelsic texture. Type III contains no detrital components and records polyphase recrystallisation. U–Th–Pb monazite dating indicates that metamorphism in the Type III rocks occurred, at least in part, at 108.1 ± 1.2 Ma. Type IV Greenland Group has partially melted. Zircon from granitoids intruding Greenland Group in the Waipuna Valley indicate Cretaceous (c. 111 Ma) emplacement. Greenland Group Types III and IV, and the granitic plutons, have been variably sheared with quartz textures indicating progressive cooling during deformation. A mylonite zone occurs just above outcrop of the Type IV rocks. Field and age relationships are interpreted to show that the Waipuna Valley exposes portions of an upper plate and lower plate to a Cretaceous ductile shear zone that is here named the Waipuna Shear Zone. The overall structure is similar to the nearby Cretaceous extensional Paparoa Metamorphic Core Complex. The Reefton Goldfield lies in the upper plate to the Waipuna Shear Zone, not far above the mylonite zone. Cretaceous metamorphism and shearing of Greenland Group could have aided formation and then transport of gold-bearing fluids into structurally higher rocks.